COMPLEX SUICIDE: MULTIPLE METHODS USED TO END LIFE (Journal of Forensic Medicine & Toxicology, 2018)
Suicide is a frequent and significant form of unnatural death, especially from the forensic perspective. Although suicide is a complex human behaviour that cannot easily be predicted, a range of factors has been shown to contribute to it. Cases with multiple simultaneous suicidal attempts are known as complex suicide. To accomplish the suicide successfully the person may attempt more than one method depending upon the situation and the plan of the suicide. In forensic practice on autopsy examination, sometimes it is difficult to differentiate between suicide, homicide, and accidental death in such cases where multiple methods are used to end life. In the case presented, the woman tried various method to commit suicide such as incised wound over the throat and other part of the body and ingestion of poisonous substance. However none of the attempts or methods proved fatal. The paper stresses that in every such case, it is necessary to differentiate between suicide and other violent forms of death after thorough examination of the scene, a meticulous autopsy and corroborative history provided by relatives and friends.
Keywords: Suicide; Complex Suicide